2003
DOI: 10.1097/00130832-200302000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Sinusitis update

Abstract: Clinical symptoms are important in making the diagnosis of rhinosinusitis and should be supported by objective findings on nasal endoscopy and, if necessary, computed tomography scans. The mainstay of treatment remains antibiotics, with a potential role for decongestants and intranasal steroids. The presence of chronic inflammation with a Th2 cytokine predominance in sinus tissues should be kept in mind, especially in patients with coexistent morbidities such as allergic rhinitis and asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
1
10
0
6
Order By: Relevance
“…Although the sample size was rather limited, it seems clear that humming nonresponders are over‐represented in rhinitis patients. Assuming that the humming test reflects sinus obstruction, this fits well with earlier studies where a CT scan has shown that sinus abnormalities are very common in this disorder [19–22]. We should, however, consider that an ineffective humming response was observed in two subjects despite the absence of complete sinus obstruction at the endoscopy, whereas humming remained effective in one subject with severe turbinate hypertrophy, implying that other factors might modulate the effectiveness of humming manoeuvre on sinus NO release.…”
Section: Discussionsupporting
confidence: 86%
“…Although the sample size was rather limited, it seems clear that humming nonresponders are over‐represented in rhinitis patients. Assuming that the humming test reflects sinus obstruction, this fits well with earlier studies where a CT scan has shown that sinus abnormalities are very common in this disorder [19–22]. We should, however, consider that an ineffective humming response was observed in two subjects despite the absence of complete sinus obstruction at the endoscopy, whereas humming remained effective in one subject with severe turbinate hypertrophy, implying that other factors might modulate the effectiveness of humming manoeuvre on sinus NO release.…”
Section: Discussionsupporting
confidence: 86%
“…A great deal has been written regarding the role of defects in mucociliary clearance and humoral immune deficiency as contributive factors to rhinosinusitis. These have been extensively reviewed in recent articles 12,[157][158][159][160][161][162][163] and were therefore not discussed at length at the conference.…”
Section: Aspirin-exacerbated Respiratory Diseasementioning
confidence: 99%
“…The recent appreciation that exposure to noninfectious inflammatory agents may predispose a person to infectious rhinosinusitis has stimulated renewed interest in the role of inflammatory mediators and inflammatory cells in the pathogenesis of rhinosinusitis [2, 3]. Many trials have highlighted the potential of inflammatory mediators for the treatment of inflammatory diseases, including rhinosinusitis [48].…”
Section: Introductionmentioning
confidence: 99%